Peran Konten Marketing dalam Kualitas Produk di Aplikasi TikTok - Nanda Silvia Galingging; April Laksana; Miftahus Sa'adah; Eva Nurhaliza (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
This research which discusses the role of content marketing in product quality in the TikTok application has a significant influence on the perception of product quality in TikTok. The majority of respondents stated that creative and relevant content influenced their perspective on product quality, tended to rate positively when the content presented could attract attention with clear information and build emotional connections. Further analysis of TikTok video content shows success based on the utilization of trends, selection of appropriate narratives, use of features such as hastag challenges. However, the success of content cannot be separated from a deep understanding of the target audience, therefore brand personalization must be a balance between entertainment and promotion.